Hands-On Blockchain with Hyperledger : Building Decentralized Applications with Hyperledger Fabric and Composer. - Baset, Salman (Packt Publishing Ltd, 2018)
With concrete exercises and examples this book will help you to understand how to deploy a Hyperledger Fabric network. It then proceeds to explain the steps in developing a full fledged decentralized application. You will not only learn how to plan, design and create private networks but also evolve the network as per organizational needs.